Social Media Marketing of Public Transportation: A Case of KAI Bandara Railink Soekarno-Hatta - Hanandito Adi Pratama; Atik Aprianingsih (STIE Amkop Makassar, 2023)
The presence of railway transportation to Soekarno-Hatta Airport, which was touted as one of the solutions to address traffic congestion, has not yielded satisfactory results. The low occupancy rate of the airport trains, which remains below 30%, indicates that the public's interest in using the train to the airport is below expectations. The competition from other modes of transportation, such as ride-hailing and regular taxis, buses, and even private cars, plays a role. Despite having sufficient infrastructure, the airport train's occupancy rate has not shown significant improvement. KAI Bandara Railink, as the operator of the airport train, should engage in extensive marketing activities to increase its usage. In the era of social media, social media platforms should serve as a marketing tool and influence individuals' decisions to use the airport train. Hence, this study examines the impact of social media marketing activities on the purchase intention of the public towards Soekarno-Hatta Airport train. By utilizing the PLS-SEM model, the results indicate that positive social media marketing activities have an influence on an individual's purchase intention through the mediating variable of brand awareness. Therefore, the author recommends focusing on improving the content of KAI Bandara Railink's social media (Instagram) to enhance public engagement.